Underwater vocalizations of Trachemys scripta elegans and their differences among sex–age groups - Zhou, Lu; Zhao, Long-Hui; Li, Handong; Wang, Tongliang; Shi, Haitao; Wang, Jichao (Frontiers in Ecology and Evolution, 2022)
The aim of this study was to identify underwater vocalizations in red-eared turtles (Trachemys scripta elegans) and assess differences between sexes and ages. We recorded the underwater vocalizations of the red-eared sliders and identified 12 call types through manual visual and aural inspection of the recordings. Similarity analysis verified that manual classification was relatively reliable. The call types of the turtle were described and displayed as spectrograms and waveforms. The turtles produced fewer high-frequency call types than low-frequency types in all recordings. Statistical analysis revealed significant differences in the frequencies and duration of the calls of red-eared turtles between different sexes and ages. Males vocalized pulse calls very frequently, whereas a high proportion of high-frequency call types was emitted by the female adult group. The male subadult group emitted higher frequencies of Type A, B, and C calls, which is in accordance with the phenomenon that vocal frequency is often inversely proportional to the turtle size. Some call types produced by red-eared turtles were above the frequency range of their known hearing range. This may have been a by-product of the sound production mechanism or it may have adaptive value in mitigating interference to communication from low-frequency noise common in natural waters in communication The behavioral implications of these vocalizations and whether turtles can hear such high sounds warrant further study.